Project Management Strategies in the Creative Economy: Strategi Manajemen Proyek dalam Ekonomi Kreatif - Musakulova Sitora Foziljonovna (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The creative economy has emerged as a knowledge-based economic model driven by human creativity, intellectual property, innovation, and digital technology, contributing to global trade, employment, and sustainable development. Specific Background: Project management in the creative economy requires adaptive methodologies due to uncertainty, rapid change, and the central role of ideas, talent, and creative freedom across sectors such as design, media, software, and cultural industries. Knowledge Gap: Despite growing recognition of innovative and flexible management approaches, the mechanisms for applying hybrid models, digital technologies, and intellectual property–oriented strategies in creative project management remain insufficiently systematized. Aims: This study reviews recent scientific literature to examine contemporary methodologies for managing projects in the creative economy and to formulate structured managerial approaches. Results: The findings identify three core components: hybrid management integrating Design Thinking, Agile, and Lean principles; an IP-centric model for monetization and legal protection; and ecosystem collaboration supported by data-driven digital distribution. These components address uncertainty management, team dynamics, resource coordination, and stakeholder communication. Novelty: The research synthesizes hybrid management logic with intellectual property orientation and digital ecosystem collaboration into a unified conceptual framework for creative project governance. Implications: The proposed framework provides guidance for structuring creative projects, supporting sustainable revenue models, fostering innovation processes, and positioning creative industries within global economic development strategies. Highlights• Identifies hybrid governance combining adaptive managerial approaches• Establishes intellectual property orientation as a monetization foundation• Integrates digital ecosystem collaboration for scalable creative ventures KeywordsCreative Economy; Project Management; Hybrid Management; Intellectual Property; Digital Ecosystem